2017
DOI: 10.4236/wjnst.2017.72010
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment Statistic Evaluation of X-Ray Fluorescence via NIST and IAEA Standard Reference Materials

Abstract: The aim of this study is a quality assessment of X-ray fluorescence laboratory located at the University of Khartoum. The X-ray fluorescence spectrometer system consists, a set of three 109 Cd sources of an initial nominal activity of 10 µCi, and Si(Li) detector Energy Dispersive XRF(EDXRF) systems. It is important to carry out this work because it has an effective contribution for a wide range of research and services. The assessment was carried out by measuring 8 NIST-2709a (soil) and 13 IAEA-155 (milk po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Especially for applications involving public funding, but generally as a consumer protection measure, these type of products should be certifiable in the same way many soil laboratories are. A usual approach is the use of reference materials (Dybczyński et al, 1979;Pueyo et al, 2001;Ahmed et al, 2017), which should be consistent with the model coverage reported. The properties measured in the reference materials should fall within the prediction interval produced by the model, with a confidence defined for each application.…”
Section: Commercial ML Applicationsmentioning
confidence: 99%
“…Especially for applications involving public funding, but generally as a consumer protection measure, these type of products should be certifiable in the same way many soil laboratories are. A usual approach is the use of reference materials (Dybczyński et al, 1979;Pueyo et al, 2001;Ahmed et al, 2017), which should be consistent with the model coverage reported. The properties measured in the reference materials should fall within the prediction interval produced by the model, with a confidence defined for each application.…”
Section: Commercial ML Applicationsmentioning
confidence: 99%
“…Specially for applications involving public funding, but generally as a consumer protection measure, this type of products should be certifiable, in the same way many soil laboratories are. A usual approach is the use of reference materials (Dybczyński et al, 1979;Pueyo et al, 2001;Ahmed et al, 2017), which should be consistent with the model coverage reported.…”
Section: Commercial ML Applicationsmentioning
confidence: 99%
“…To determine the standard uncertainty of the phase compositions, the ISO Guide to the Expression of Uncertainty Measurements (GUM) and associated methods , were used with the following formulas = 1 n i = 1 n x i s false( x i false) = i = 1 n ( x i ) 2 ( n 1 ) u = s ( x i ) n where x i is the experimental mole fraction for the i -th experiment; is the average of the mole fractions x i ; n is the number of repetitions for each tie-line; s ( x i ) is the standard deviation, and u is the standard uncertainty.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the standard uncertainty of the phase compositions, the ISO Guide to the Expression of Uncertainty Measurements (GUM) and associated methods 22,23 were used with the following formulas…”
Section: Analysis Of Phase Compositionmentioning
confidence: 99%